Strategi Komunikasi Melalui Promo Digital Untuk Meningkatkan Rating di Rajawali Televisi - Irawan, Yousep Eka; Iswardani Witarti, Denik (Avant Garde, 2023)
Television continues to look for ways to carry out its communication strategy in order to be the best in its segment by increasing ratings. In essence, communication strategy has planning and management to achieve a goal, namely optimizing the presence of technology, as well as a transfer of new ideas on a larger scale designed to change human behavior. This research is based on a qualitative approach and uses content analysis. The data was collected from April to November 2023. The data collection techniques used were interviews, observation and documentation. The research results: First, It can be concluded that the first division to manage digital promos since 2017. Initially Rajawali TV only utilized onair and offair promos. The range of promo broadcasts no longer depends on broadcast hours or broadcast slots. Second, managing promos on social media and the process of creating and processing contents so as to create interaction and get input from the audience, invite to disseminate promo content and RTV benefits from additional income from Youtube. Third, the results of social media utilization are seen to help increase ratings. However, there need to be other factors to increase program ratings consistently, such as content, program content itself, broadcast hours, geographic factors, social economic strata, competing tv factors.